KUAT TEKAN MORTAR DENGAN CANGKANG KERANG SEBAGAI SUBTITUSI AGREGAT HALUS - Arifa Nur Fadiah; Agus Murdiyoto (Construction and Material Journal, 2022)
Mortar is an especially important component used for construction. The building blocks of mortar consist of cement, fine aggregate, and water. In this study, oyster shells were used as a substitute for fine aggregate due to the increasing production of oyster shells every year, with the hope that the use of oyster shells could reduce oyster shells waste in the environment and obtain innovations for the construction world. The test objects were made in the form of a cube using a mixture ratio of 1 PC: 3 PS with variations of 0%, 5%, 10%, and 15% of shells against the weight of sand with a test time of 3 days, 14 days, and 28 days. Before making the test object, the mortar constituent materials were tested first, then the mortar design was carried out after all the constituent materials met the requirements. This study also used SPSS software to determine the effect of using shells as a substitute for fine aggregate on the compressive strength of mortar. From this study, it was found that the effect of oyster shells substitution was 17.6% at the age of 28 days compared to mortar without shells. The use of oyster shells can increase the compressive strength of mortar up to 97.6% at the age of 28 days. A variation of 15% was found at the age of 28 days as a variation with a maximum compressive strength value of 18.06 MPa. Keywords: Compressive Strength, Mortar, Oyster Shells.